Winning the war of perception: american attempts to counter Germany's military influence in Turkey during World War II. (2nd January 2016) - Avcı, Ayşegül
ABSTRACT: This article analyzes the emergence of the USA as a political power on the international platform against Germany in order to break the strong influence of the latter in Turkish military spheres. Turkey did not enter World War II, but it witnessed a war of perception, conducted by these two opposing powers to gain the trust of the Turkish statesmen. To accomplish that, in the early years of the war, the USA began sending experts to train Turkish military officers, and civilian and military students, and offered the opportunity to get educated at American institutions. During the war, the USA also tried to strengthen its influence by inviting journalists and military staff to observe technological advancements at factories, and victories in the fronts, and by showing movies presenting the power of the Allied armed forces.